(untitled) (Academic Journal of Internal Affairs, 2020)
The different service branches of the US armed forces have been supporting the border protection operations at the US-Mexican border with direct presence for almost 2 years now. This unusual deployment of the armed forces faced sincere legal and professional critics, mainly because of the operations’ aim, the financial background and their effectiveness. I will shortly introduce the measures and steps which has been taken from 2018, especially the changing task framework, and the challenges of the current world pandemic situation.